Vanitas vanitatum et super omnia vanitas: The astronomer Heinrich Selder and a newly discovered fourteenth-century critique of astrology - Nothaft, C (Brill Publishing, 2016)
A previously unknown treatise on historical chronology (Tractatus de tempore dominice annunciationis, nativitatis et passionis), written by a southern German author between 1371 and 1378, preserves an unusually sophisticated and penetrating scholarly critique of astrology. The main purpose of this article is to introduce and analyze this important work, which is characterized by its close attention to technical astronomical detail and the use of empirical data to refute astrological doctrines. Comparison will be made to the contemporary anti-astrological works of Nicole Oresme and Heinrich of Langenstein, from which the newly discovered Tractatus differs in a number of significant aspects, underscoring its originality. It will be argued that this anonymously transmitted work was authored by the obscure Swabian astronomer Heinrich Selder, whose Canones tabularum Alphonsinarum (1365) are noteworthy for their critical remarks on the Alfonsine Tables.